Guidance for studies evaluating the accuracy of tuberculosis triage tests - Nathavitharana, Ruvandhi R.; Denkinger, Claudia M. (The journal of infectious diseases, 2019)
Abstract. Approximately 3.6 million cases of active tuberculosis (TB) go potentially undiagnosed annually, partly due to limited access to confirmatory diagnos